Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1093/eurjhf/hfq115
|View full text |Cite
|
Sign up to set email alerts
|

The Intermountain Risk Score (including the red cell distribution width) predicts heart failure and other morbidity endpoints

Abstract: AimsThe complete blood count (CBC) and basic metabolic profile are common, low-cost blood tests, which have previously been used to create and validate the Intermountain Risk Score (IMRS) for mortality prediction. Mortality is the most definitive clinical endpoint, but medical care is more easily applied to modify morbidity and thereby prevent death. This study tested whether IMRS is associated with clinical morbidity endpoints. Methods and resultsPatients seen for coronary angiography (n ¼ 3927) were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
73
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 25 publications
6
73
0
3
Order By: Relevance
“…Nevertheless, the role of RDW as a predictor of mortality in different groups of patients has been widely described. RDW has also been included as a key element of the scales based on complete blood counts assessing the risks of mortality and morbidity [28,29]. Therefore, on the basis of this work, it appears that RDW may be helpful in selecting a group of patients with a higher risk for postoperative complications requiring additional attention in being qualified for surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, the role of RDW as a predictor of mortality in different groups of patients has been widely described. RDW has also been included as a key element of the scales based on complete blood counts assessing the risks of mortality and morbidity [28,29]. Therefore, on the basis of this work, it appears that RDW may be helpful in selecting a group of patients with a higher risk for postoperative complications requiring additional attention in being qualified for surgery.…”
Section: Discussionmentioning
confidence: 98%
“…4 IMRS research led to the discovery that the red cell distribution width (RDW) predicts mortality. [4][5][6] IMRS also predicts common morbidity end points that lead to mortality, including COPD. 50 The finding that IMRS is associated with COPD raised the questions of whether IMRS, its components, or a rederivation of IMRS that integrated PFT variables could predict mortality in a pulmonary population.…”
mentioning
confidence: 99%
“…Many studies have shown that RDW is a strong predictor of adverse outcomes in patients with heart failure, stroke and myocardial infarction (4)(5)(6). In previous studies, in patients undergoing coronary angiography and CABG indicated a possible association between RDW and AF (7,8).…”
Section: Introductionmentioning
confidence: 97%